Deixadas para trás? Um estudo sobre a persistente falta de espaço das mulheres no mercado de trabalho brasileiro e a igualdade de gênero - Nunes, Alessandra Garcia Machado (2022)
The entry of women into the world of work can be understood as a milestone in the debate on gender equality in Brazilian society. Over the decades, especially the last five, the numerous reflections on the conditions of women's work have enabled a detailed design of the different forms of participation of women in this. Still, the barriers remain, evidencing gender bias in how the various occupations are distributed in society. In this sense, even though women have advanced, even though they have occupied the public space and started to perform productive work, they are more susceptible to loss of space in the labor market, even with governmental and non-governmental bodies promoting the quest for gender equality. Therefore, the present research aimed to analyze the reasons for the persistent lack of space for women in the Brazilian labor market, despite advances in debates and efforts to promote gender equality in society. Specifically, it had two objectives: to understand, from the perspective and expertise of researchers from federal universities of the Rio Grande do Sul, the reasons for the lack of space for women in the Brazilian labor market, even with the efforts to promote gender equality, and also to verify, the from the point of view of Brazilian researchers who study the topic of gender and the labor market, the reasons why women face challenges and do not increase space in the Brazilian labor market. Therefore, this research is characterized as descriptive-exploratory, with a mixed approach, and the mixed method was used with a sequential exploratory strategy. In the first one, a qualitative phase was carried out, and from the first results of the same, the quantitative phase was operationalized. The data collection technique for the qualitative stage was the Delphi technique, which had two rounds, had seven subjects, and was analyzed by content analysis. The collection took place through a questionnaire for the quantitative phase, resulting in 451 respondents. The study was carried out using descriptive statistics. Concerning the main results achieved in an integrated way (qualitative and quantitative results), they expressed that male domination causes women to be assigned social roles and poses different obstacles to women's careers. Even with the insertion of women in the world of work, it is marked by inequalities, discrimination, stereotypes, difficulty in ascending, difficulty in achieving leadership, excessive responsibility for domestic and care work, precariousness, informality, disparities, and, when associated, if it's race and class, the problems magnify. The promotion of gender equality, even the policies created, is not enough to extinguish years of domination and structural issues in Brazilian society. These results lead us to reflect on whether women never had a real place in the Brazilian labor market since the evidence demonstrates the maintenance of barriers for 50 years.